Is AI Better at Detecting Heart Disease? A Professional Review of Machine Learning in Cardiology - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The global burden of cardiovascular disease CVD remains one of the most significant public health challenges, accounting for millions of deaths annually. In ...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Precision Medicine